Black hole as a wormhole factory - Sung-Won Kim; Mu-In Park (Physics Letters B, 2015)
There have been lots of debates about the final fate of an evaporating black hole and the singularity hidden by an event horizon in quantum gravity. However, on general grounds, one may argue that a black hole stops radiation at the Planck mass (ħc/G)1/2∼10−5 g, where the radiated energy is comparable to the black hole's mass. And also, it has been argued that there would be a wormhole-like structure, known as “spacetime foam”, due to large fluctuations below the Planck length (ħG/c3)1/2∼10−33 cm. In this paper, as an explicit example, we consider an exact classical solution which represents nicely those two properties in a recently proposed quantum gravity model based on different scaling dimensions between space and time coordinates. The solution, called “Black Wormhole”, consists of two different states, depending on its mass parameter M and an IR parameter ω: For the black hole state (with ωM2>1/2), a non-traversable wormhole occupies the interior region of the black hole around the singularity at the origin, whereas for the wormhole state (with ωM2<1/2), the interior wormhole is exposed to an outside observer as the black hole horizon is disappearing from evaporation. The black hole state becomes thermodynamically stable as it approaches the merging point where the interior wormhole throat and the black hole horizon merges, and the Hawking temperature vanishes at the exact merge point (with ωM2=1/2). This solution suggests the “Generalized Cosmic Censorship” by the existence of a wormhole-like structure which protects the naked singularity even after the black hole evaporation. One could understand the would-be wormhole inside the black hole horizon as the result of microscopic wormholes created by “negative” energy quanta which have entered the black hole horizon in Hawking radiation process; the quantum black hole could be a wormhole factory! It is found that this speculative picture may be consistent with the recent “ER=EPR” proposal for resolving the black hole entanglement debates.